A Unified Dual Active Bridge Model Based on Improved Extended Describing Function With Dead Time Compensation for Electric Vehicles - Deshu Zhang; Houji Li; Jie Chen (IEEE Access)
Dual active bridge (DAB) converter is well suited for deriving a high-power density plug-in hybrid electric vehicle charger. In this case, various DAB operation modes have to be considered, but few papers have established a unified DAB model. Meanwhile, the failure of zero voltage switching (ZVS) operation during the dead time would distort the ideal phase shift angles, deviating the actual DAB state from analysis in previous modeling methods. This article puts forward a substantial effort to address all the above-mentioned hurdles by proposing a unified DAB model with dead time compensation for all operating modes and firstly introducing the improved extended describing function (IEDF) to DAB modeling. Two improvements compared with the traditional functions are implemented: First, due to the high-frequency and non-sinusoidal characteristics of DAB inductor current, the influence of incorporating higher-order harmonics is quantitatively studied, and it is proved that the maximum output voltage error of the IEDF based DAB steady-state model occurs at light load in single phase shift control; Second, the influence of zero voltage switching (ZVS) failure on DAB voltage gain is also studied and the steady- and dynamic-states’ model accuracy of the IEDF based DAB model is greatly improved. Finally, simulations and experiments are carried out with a 2-kW prototype, and the proposed model shows great accuracy in both steady- and dynamic-states characteristics.